ANOMALI GAS RADON SEBAGAI PREKURSOR GEMPABUMI DI SEKITAR SESAR PALUKORO - Sulastri, Sulastri; Nursarifa, Saskia; Sunardi, Bambang; Rohadi, Supriyanto; Nugroho, Cahyo; Perdana, Yusuf Hadi (Pusdiklat BMKG, 2020)
Radon gas concentration anomalies before the occurrence of earthquakes have been detected in many majoearthquake cases in the world, so they can be considered as early signs or earthquake precursors. The BMKGhas installed a radon gas concentration measuring device equipped with gauges of air pressure, air temperatureand rainfallaround the Palukoro Fault, namely at the Tadulako Earthquake Precursor Station. This study aims todetermine the existence of earthquake precursors around the PaluKoro Fault recorded by the Tadulako PrecursorStation, by utilizing the radon and air pressure sensors installed at the station. The data used are radon data and air pressure data in 2016 as well as data on earthquake events that occurred around the Palukoro Fault in thesame year.The data analysis method was carried out in three stages. First, the selection of an earthquake with acertain distance from Tadulako, where the possibility of the radon precursor can still be detected. Second, analysiof radon data anomalies using statistical methods, namely outside the mean ± 2 standard deviations, and lookingat earthquake data that corresponds to the radon anomaly. Third, selecting radon anomalies which are consideredas earthquake precursors whose rate of change is inversely proportional to the rate of change in air pressureThe analysis results show 9 radon gas anomalies detected in the second step and 4 radon gas anomalies thatfulfill the third step. This method needs to be tested on radon and air pressure data from BMKG precursor stationselsewhere.